Outcome Following Medical and or Surgical Intervention (ESPAL) for the Treatment of Epistaxis in ENT Unit in Al-Diwaniyah Teaching Hospital: Cohort Study - Ali Najm Abdullah Alibadi1 , Wasam Abbas Abdulhsen Albusalih1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim of the study: In the current study the aim was to evaluate a sample of Iraqi patients with epistaxis regarding medical and surgical interventions and their outcomes. The study was carried out in Ear Nose and Throat (ENT) unit in Al-Diwaniyah Teaching Hospital, Mid-Euphrates region, Iraq. The study started on January 2018 and ended on June 2019. The main variables included in the study were age, residency, level of education, occupation, clinical presentation (cold versus emergency), severity of bleeding, type of intervention (Medical versus surgical), presence or absence of associated disease and response to treatment. Medical intervention included, direct pressure, anterior nasal packing and chemical cauterization with silver nitrate; whereas, surgical intervention included transnasal endoscopic sphenopalatine artery ligation (TESPAL). Bleeding was more frequently of emergency presentation rather than cold in association with surgical group, more severe in surgical group and characterized by more frequent attacks per month in surgical group in comparison with medical group. Response to medical and surgical intervention was good and satisfactory in all patients even after follow up for 6 months at least. There were negligible adverse effects in association with surgical intervention.